Differences in knowledge of female athlete triad and relative energy deficiency in sport in female cross-country athletes - Lodge, M. T.; Ackerman, K. E.; Garay, J. (Journal of Athletic Training, 2024)
Background: The female athlete triad (Triad) and relative energy deficiency in sport (REDs) describe potential health and performance consequences of low energy availability. Objective: We surveyed female cross-country athletes to assess differences in educational impact scores (EIS; knowledge score × confidence score factor) of Triad and REDs. Associations between EIS and participant characteristics (eg, mileage [current and peak], years of running experience, age, bone stress injury history, division level participation, academic area of study, Triad or REDs diagnoses, and Triad or REDs education) were explored. Main Outcome Measure(s): An evidence-based online survey was developed and administered via Qualtrics to female collegiate cross-country athletes (n = 275; age = 20 ± 1 years). Results: A weak correlation existed between peak career mileage and EIS (r = 0.195; P = .010). Educational impact scores significantly differed in athletes with a related academic area of study versus those without (21.91 ± 5.16 and 16.11 ± 5.54, respectively). Educational impact scores significantly differed in athletes with Triad and REDs diagnoses (21.69 ± 5.85 and 22.58 ± 6.82, respectively) versus those without (16.80 ± 6.54 and 17.20 ± 6.34, respectively). Educational impact scores were higher in those who had received Triad education versus those who had not (21.03 ± 6.86 and 18.12 ± 6.82, respectively). A significant interaction between peak career mileage and Triad diagnosis was found (P = .005). Conclusions: Significant education-based and diagnosis differences suggest that Triad diagnoses correlate with peak career mileage. These findings support the facilitation of education to improve not only the treatment but also the prevention of Triad and REDs.